Noble metal nanoparticles in agriculture: impacts on plants, associated microorganisms, and biotechnological practices - Burketová, Lenka; Martinec, Jan; Siegel, Jakub; Macůrková, Anna; Maryška, Lukáš; Valentová, Olga (Biotechnology advances, 2022)
Within the past decades, nanoparticles (NPs) have become common components of electronics, batteries, cosmetics, clothing, and even dietary supplements. Despite their undisputed advantages consisting in the possibility of engineering their novel physical, thermal, optical, and biological properties, safety questions arise concerning their wide exploitation. NPs interact with living organisms, which can interfere with essential life processes. The aim of this paper is to critically review the current literature dealing with noble metals' NPs (NM-NPs) and their effects on plants and associated microorganisms. Particular attention has been given to the less studied NPs of platinum group elements, which can be considered a neglected pollutant, since they are released from vehicles' catalysts. In addition, we have provided a comprehensive overview of the biotechnology exploitation of NM-NPs in plant cultivation, where prospective nanomaterials developed as nanofertilizers and nanopesticides are introduced, and both the pros and the cons of nanomaterial plant treatments have been discussed.
Keywords: biotechnologie; rostliny; zemědělství; Silver nanoparticles; Plants; prospektivní studie; Prospective Studies; Gold nanoparticles; Metal Nanoparticles; kovové nanočástice; Microbiome; Agriculture; Biotechnology; Platinum group elements’ nanoparticles